Visualising communication ethics in the 2024 fourth vice-presidential debate - Ririt Yuniar; Titania Fattiha Ahsan; Aurelia Nadiah Kirana (Jurnal Studi Komunikasi, 2024)
There appears to be a generational gap between generations during the 4th vice-presidential candidate debate, which has the potential to be in the public spotlight during the 2024 election due to the instances of unethical communication of the candidate pairs. Three important points to be answered: First, explaining the dynamics of the debate in various perspectives between generations both visually and verbally (body language and diction used during rhetoric); Second, explaining the substance of the debate on communication ethics and verbal politeness in the context of the vice-presidential debate; Third, exploring the visual elements of both the visible and underlying aspects of the vice-presidential debate. A qualitative explanatory approach was employed in this research with data collection of YouTube video documentation categorised based on the concept of verbal politeness and the visual world according to the content analysis of the debate event video. The findings of the data display are associated with verbal politeness, ethics, and visual communication in the visual world (performance consisting of visible and invisible visual structures), which are based on the social culture and political reality of the vice-presidential candidates who have an important role in filling the gap between generations as a representation of the prospective leader of the nation. In conclusion, the communication process of debating requires ethics, self-control, represented in the polite attitudes and words of the three prospective leaders with the principles of mutual understanding, knowledge, self-control, humility, and wisdom. However, different generations do not need to underestimate or bring each other down. It is mandatory to have the principle of upholding equal human dignity so that the purpose of communication as information, persuasion, and education achieves the content of the message as a quality debate.